The value of Olexander Rayevskiy's scientific work for the development of Ukrainian psychology - Yablonska, T. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article is dedicated to the importance of scientific work of Professor O. Rayevskiy for the establishment and development of national psychology, including its development in the Kyiv University. Presented the main trends of growth of psychological knowledge in Ukraine during the twentieth century – features content areas of psychological research, specific university teaching at different times. Analysed the features O. Rayevskiy's formation as a scientist, teacher, his professional way, different directions of his activity and O. Rayevskiy's main achievements. Presented the role of scientist as one of the founders of the Department of Psychology, National University of Kyiv. The article is presented the importance of O. Rayevskiy's scientific creativity for the development of Kyiv psychological school and national psychology in general. Analysed the problems of scientist's psychological research, presented the main ideas of his works and their development in modern psychological research.
Keywords: formation of psychology; development of Ukrainian psychology; Kyiv University; Kyiv psychological school; Olexander Rayevskiy